Foundations of leadership : principles, practice, and progress - Guthrie, Kathy L.; Devies, Brittany (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"This book explores the foundations of leadership by confronting common assumptions and provides language for engaging in the leadership process as a leader and a follower. This practical book was designed for college students who are interested in learning more about the process of leadership, leaders in formal and informal roles, as well as educators and professionals who work with student leaders on college campuses. However, this book is also accessible to high school students, as well as graduate students ready to focus on their leadership learning. Foundations of Leadership: Principles, Practice, and Progress frames leadership as a process in which followers and leaders engage in a specific context. It offers learning opportunities for students to personally reflect, engage with others, and sharpen their own leadership practice. Each chapter focuses on important foundational topics of leadership with features to engage readers to getting the most out of this book. Features include chapter framing at the beginning of each chapter to prepare for learning and stopping points to reflect on their learning throughout the chapters. Each chapter concludes with questions for students to reflect on their own, discussions questions for reflection with others, and activities to take their leadership learning a "level up." This book is designed to be accessible for students in a classroom setting, student organizations, community groups, and individual learning opportunities"-- Provided by publisher.
Keywords: Leadership.; Educational leadership.; Psychology -- Social Psychology.; Social, group or collective psychology.; elektronické knihy; electronic books